The effects of computer-based cognitive training on attention and working memory in Thai older adults with mild cognitive impairment - Chumpurat, Napat; Munkhetvit, Peeraya; Wongpakaran, Nahathai; Rattakorn, Phuanjai (Journal of Associated Medical Sciences, 2025)
Background: Mild cognitive impairment (MCI) is an intermediate state occurring between healthy aging and dementia among the elderly which result in cognitive, especially regarding attention and working memory. However, the declined state can be abated if training or stimulations are promptly promoted by a computerbased cognitive training program. Objective: The aim of this study was to explore the effects of the Neofect Cognition as a computer-based cognitive training program on attention and working memory in Thai older adults with MCI. Materials and methods: Twenty-three Thai older adults with MCI were divided into two groups; the experimental group (N=13) receiving the Neofect Cognition program for 6 executive weeks, 3 times per week, 45 minutes per session, and the control group (N=10) receiving education about MCI. Data was collected by assessing before and after participating in the program using the Trail Making Test (TMT) and the Memory subtest of the Thai Cognitive-Perceptual Test (Thai-CPT). Results: The results showed that the experimental group had a statistically significant difference of attention (TMT-B) and working memory scores, while the control group had no statistically significant difference for both attention and working memory. Furthermore, there was a significant difference between the groups in attention (TMT-B) and working memory. Conclusion: From the results, it can be stated that the computer-based training program (Neofect Cognition) might improve attention and working memory in Thai older adults with MCI.